Perkembangan Kreatif Musik Gamat di Sumatera Barat - Yade Surayya; Fahmi Marh (SENDRATASIK UNP, 2022)
This article is the result of research on the creativity development of traditional music which tends to lead to adjustments to the appreciation of the dynamic contemporary society as the basis for cultivating today's music. In general, this study examines one of the developments of musical creativity in Minangkabau, namely Gamat music. The research uses approaches from various scientific disciplines. It can also be said that this research is a combined research. Using various data sources that can be obtained through written sources in the form of books, articles, and scores. This method is carried out because research on Gamat music in Minangkabau has been carried out by many other researchers. The development of traditional music is based on the openness of the Minangkabau people to new things, based on the basic lines of adaik nan taradaik and adaik istiadaik which are included in the tradition of the babuhua sintak. This custom develops creatively towards perfection, which is very elastic. In the customs contained freedom and rights in the nagari based on consensus to be creative. It grows naturally, but it is immediately removed if it is against the applicable rules. This uniqueness allows people and individuals to be as creative as possible, so it is not surprising that Gamat music can be accepted and made into traditional music in several areas in Minangkabau. The phenomenon of the development of social music that occurs among the people in Minangkabau is an interaction or response from the community itself to changes in creativity.